Kinematics and angular momentum contributions to the toe-on Tkachev on uneven bars in female gymnastics - Irwin, G.; Manning, M.; Kerwin, D. G. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The purpose of this study was to explain the mechanics of the Toe-on Tkachev on Uneven Bars, and identify whether this variant creates the release characteristics needed to perform more complex aerial body positions (e.g. straight). Images of 5 Toe-on Tkachev's performed at the 2007 World Championships were recorded with twin video cameras (50Hz). Digitising and 3D DLT techniques were combined with inertia modelling to develop customised profiles for the gymnasts. Greater flight time and angular momentum (L) suggest this variant may provide the gymnast with the opportunity to perform more complex aerial shapes. The dominant role of the hip in the creation of L was highlighted.